Acoustic metamaterials and phononic crystals - Boechler, N.; Bou Matar, O.; Daraio, Chiara 1978-; Deymier, Pierre A.; Djafari Rouhani, Bahram (Heidelberg : Springer, 2013)
This comprehensive book presents all aspects of acoustic metamaterials and phononic crystals. The emphasis is on acoustic wave propagation phenomena at interfaces such as refraction, especially unusual refractive properties and negative refraction. A thorough discussion of the mechanisms leading to such refractive phenomena includes local resonances in metamaterials and scattering in phononic crystals.
La función de los autores fue determinada por el catalogador
Keywords: METAMATERIALES; MATERIALES ACÚSTICOS; RESONANCIA PARAMAGNÉTICA ACÚSTICA